Cerebral Metastasis: Case Series Cerebrum as a Safe Haven (Global Journal of Medical Research, 2014)
Cerebral metastasis may be a common manifestation of systemic diseases. Cerebral metastasis are reported in 15-25 percent of patients with Brain tumors. Parenchymal blood flow is an important regulator of metastasis and most of the metastatic lesions are found in the cerebrum .most brain metastasis arise by hematogenous dissemination followed by dessimination through CSF.
Keywords: metastasis; cerebral; cerebellum; MRI; disseminate; microinvasion